2022
DOI: 10.1021/acs.nanolett.2c02427
|View full text |Cite
|
Sign up to set email alerts
|

Superradiance and Exciton Delocalization in Perovskite Quantum Dot Superlattices

Abstract: Achieving superradiance in solids is challenging due to fast dephasing processes from inherent disorder and thermal fluctuations. Perovskite quantum dots (QDs) are an exciting class of exciton emitters with large oscillator strength and high quantum efficiency, making them promising for solid-state superradiance. However, a thorough understanding of the competition between coherence and dephasing from phonon scattering and energetic disorder is currently unavailable. Here, we present an investigation of excito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 48 publications
5
29
0
Order By: Relevance
“…We then correlated the low-temperature PL linewidth to the structural properties obtained from STEM-FFT analysis. In molecular J- and H-aggregates with exciton delocalization, PL linewidth is inversely proportional to the number of coupled emitters, a phenomenon known as exchange narrowing. PL linewidths for CsPbBr 3 SLs also exhibit exchange narrowing below 100 K commensurate with their degree of coherence, though some convolution with inhomogeneous broadening is present (Figure S9e, Supporting Information Section S4). , Surveying our population of SLs, we find that PL linewidth has no correlation to FFT linewidth, the primary metric for disorder in the SL assembly (Figure b). In other words, the extent of exciton delocalization at low temperatures is not dictated by long-range structural order in the SL.…”
Section: Correlating Sl Structure To Optical Propertiesmentioning
confidence: 87%
See 4 more Smart Citations
“…We then correlated the low-temperature PL linewidth to the structural properties obtained from STEM-FFT analysis. In molecular J- and H-aggregates with exciton delocalization, PL linewidth is inversely proportional to the number of coupled emitters, a phenomenon known as exchange narrowing. PL linewidths for CsPbBr 3 SLs also exhibit exchange narrowing below 100 K commensurate with their degree of coherence, though some convolution with inhomogeneous broadening is present (Figure S9e, Supporting Information Section S4). , Surveying our population of SLs, we find that PL linewidth has no correlation to FFT linewidth, the primary metric for disorder in the SL assembly (Figure b). In other words, the extent of exciton delocalization at low temperatures is not dictated by long-range structural order in the SL.…”
Section: Correlating Sl Structure To Optical Propertiesmentioning
confidence: 87%
“…More recently, our group showed that CsPbBr 3 cubic SLs also exhibit single-photon superradiance arising from exciton delocalization at low excitation fluence. Unlike superfluorescence, superradiance does not require a light-induced phase-synchronization of emitters . However, we found that the number of coherent emitters in the superradiant state varied widely across SLs grown under the same conditions, which was reflected in their heterogeneous photoluminescence (PL) spectra and lifetimes at low temperatures.…”
mentioning
confidence: 82%
See 3 more Smart Citations